The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.expneurol.2006.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The HSV-2 protein ICP10PK prevents neuronal apoptosis and loss of function in an in vivo model of neurodegeneration associated with glutamate excitotoxicity

Abstract: Excessive glutamate receptor activation results in neuronal death, a process known as excitotoxicity. Intrastriatal injection of N-methyl-D-aspartate (NMDA) is a model of excitotoxicity. We used this model to examine whether excitotoxic injury is inhibited by the anti-apoptotic herpes simplex virus type 2 (HSV-2) protein, ICP10PK, delivered by the replication incompetent HSV-2 vector, ΔRR. Intrastriatal ΔRR administration (2500 plaque forming units) was nontoxic and did not induce microglial activation five da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 45 publications
5
39
0
1
Order By: Relevance
“…For HSV-2, besides US3 (Asano et al, 1999(Asano et al, , 2000Hata et al, 1999;Murata et al, 2002), ICP10 (Golembewski et al, 2007;Perkins et al, 2002aPerkins et al, , b, 2003 has been reported to protect cells from apoptosis. It will be interesting to dissect the potential anti-apoptotic function of different PRV proteins and to determine their combined effect on infectious virus production.…”
mentioning
confidence: 99%
“…For HSV-2, besides US3 (Asano et al, 1999(Asano et al, , 2000Hata et al, 1999;Murata et al, 2002), ICP10 (Golembewski et al, 2007;Perkins et al, 2002aPerkins et al, , b, 2003 has been reported to protect cells from apoptosis. It will be interesting to dissect the potential anti-apoptotic function of different PRV proteins and to determine their combined effect on infectious virus production.…”
mentioning
confidence: 99%
“…Previous studies had shown that ICP10PK overrides caspase-dependent cascades, [11][12][13][14][15][16][17] but its ability to inhibit caspase-independent death programs is still unknown. In a first series of experiments to address this question, neuronally differentiated PC12, PC139 and PC47 cells were treated with MPP+, exposed to the mitochondrionselective dye MitoTracker Red 580 and stained with Alexa Fluor 488-labeled AIF antibody, as described in 'Materials and methods'.…”
Section: Icp10pk Inhibits Mpp+-triggered Aif Release/nuclear Translocmentioning
confidence: 99%
“…To examine whether ICP10PK inhibits MPP+-induced cell death, neuronally differentiated PC12 cells were treated with the ICP10PK vector DRR, that is neuroprotective in other toxicity paradigms, 11,[13][14][15][16][17] and exposed to MPP+ (1 mM, 24 h) at 24 h after infection. PCD was evaluated based on DNA fragmentation measured by terminal transferase dUTP nick-end labeling (TUNEL).…”
Section: Icp10pk Inhibits Mpp+-induced Toxicitymentioning
confidence: 99%
See 2 more Smart Citations